Hasil Belajar Kognitif Materi Geografi Kelas X Menggunakan Model Computer-Supported Collaborative Learning (CSCL) - Pratiwi, Rantian Virta Eka; Hotimah, Oot; Sucahyanto, Sucahyanto (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study explores the impact of Computer-Supported Collaborative Learning (CSCL) on cognitive learning outcomes in 10th-grade Geography, focusing on atmospheric dynamics. The research conducted at SMA Negeri 60 Jakarta utilized a quasi-experimental design with class X-4 (CSCL model) as the experimental group and class X-3 (Discovery Learning model) as the control group.The CSCL model, emphasizing collaborative learning through digital tools, significantly improved cognitive outcomes compared to the control group. Validation of the research instrument confirmed its reliability and validity. Normality and homogeneity tests ensured the appropriateness of the data. In conclusion, CSCL positively influences students' cognitive learning in geography. Recommendations include further exploration of CSCL's effectiveness, analysis of additional learning aspects, encouragement of teacher adoption, and future research on CSCL's broader implementation.